A transformless electric spring with decoupled real and reactive power control - Qi, Yang (2019)
The electric spring has emerged as a promising technique to stabilize electrical grids with high penetration of renewable energy sources. In response to the grid frequency deviation, electric springs can flexibly regulate the noncritical load power. However, the previous versions of electric springs either suffer from the coupling effect between real and reactive powers, or require associated energy storage systems, or need an extra low-frequency transformer for the isolation purpose. To overcome these shortcomings, a transformless electric spring and its associated control strategy are proposed in this paper. The proposed electric spring can independently regulate the real and reactive power without using batteries for maintaining the DC-link voltage or handling power flow. Finally, real time hardware-in-loop (HIL) simulation results are provided for verification.